2022
DOI: 10.3390/molecules27061973
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Cognition of Decitabine: Insights into Immunomodulation and Antiviral Effects

Abstract: DNA methylation, as one of the major means of epigenesis change, makes a large difference in the spatial structure of chromatin, transposable element activity and, fundamentally, gene transcription. It has been confirmed that DNA methylation is closely related to innate immune responses. Decitabine, the most efficient available DNA methyltransferase inhibitor, has demonstrated exhilarating immune activation and antiviral effects on multiple viruses, including HIV, HBV, HCV, HPV and EHV1. This review considers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…When a ribose/deoxyribose group is attached to this molecule (Fig. 1a), it becomes two inhibitors for nucleic acid methylation (2), which can promote a variety of cellular stress responses such as apoptosis, autophagy and senescence (3,4). Meanwhile, they have been demonstrated to be functional as important chemotherapeutic drugs in the clinic treatment of myelodysplastic syndromes (MDS) (5) and acute myelogenous leukemia (2,5).…”
Section: Introductionmentioning
confidence: 99%
“…When a ribose/deoxyribose group is attached to this molecule (Fig. 1a), it becomes two inhibitors for nucleic acid methylation (2), which can promote a variety of cellular stress responses such as apoptosis, autophagy and senescence (3,4). Meanwhile, they have been demonstrated to be functional as important chemotherapeutic drugs in the clinic treatment of myelodysplastic syndromes (MDS) (5) and acute myelogenous leukemia (2,5).…”
Section: Introductionmentioning
confidence: 99%
“…Decitabine may act as a nucleic acid drug, which has similar functions with anti-virus drugs. The research of Xiao J et al confirmed that decitabine showed potential antiviral activity by up-regulating the innate antiviral immune response (33).…”
Section: Discussionmentioning
confidence: 97%
“…Decitabine (DTB) has been identified as the most effective compound against EHV-4 in vitro. This compound is a deoxycytidine analog and hypomethylating agent used in the treatment of myelodysplastic syndromes [45,62]. In mice, the toxic concentration of decitabine was estimated to be 25 µM [63].…”
Section: Discussionmentioning
confidence: 99%